PTU-050 Is current UK colonoscopy training fit for purpose? – results of the 2014 BSG training survey. (22nd June 2015) - Chadwick, G; Budihal, S
Abstract : Introduction: JAG was established in 1994 and placed emphasis on improving standards of endoscopy training, with formal certification of competence. Previous surveys of trainees have suggested that access to training is variable and has been diminished by the European Working Time Directive (EWTD) and general medicine commitments. 1 Since 2011, the process for certification in colonoscopy changed to a two stage sign off; provisional certification allowing independent practice providing a trainer is immediately available, and full sign off. The 2014 BSG training survey investigated access to endoscopy training, JAG certification and barriers to endoscopy training among UK trainees. Method: Data was collated from the BSG Training survey, which was sent to all UK Gastroenterology higher specialist trainees (June–August 2014). This study investigated access to endoscopy lists, and JAG certification in colonoscopy by trainee grade. Results: 32.6% (263/806) of UK trainees responded to the survey. Training grade distribution: 32% ST3/4, 41% ST5/6, 14% ST7/8, 13% other. Reported access to endoscopy training was limited with 47% of trainees reporting attending less than 2 endoscopy lists per week, and 39% of trainees currently in training posts have access to less than 1 training list per week. 55% of trainees report using annual leave and zero days to gain additional endoscopy training, a significant increase from 31% of trainees in the 2012 survey (P < 0.001). Median numbers of colonoscopies performed at senior training grades are ST5–190, ST6–280, ST7–500. Only 45% of ST6 trainees achieved provisional certification and 21% full colonoscopy certification, with a third of ST7 trainees having not completed full colonoscopy certification by their final few months of training (Figure 1) . Reported barriers to endoscopy training include GIM commitments and the impact of the EWTD. Conclusion: Access to endoscopy training lists is inadequate, with 39% of trainees not having access to the minimum 1 training list per week recommended by JAG. 2 This has resulted in a significant numbers of trainees failing to progress from provisional to full JAG certification in colonoscopy by the end of training. Barriers to access to training need urgent investigation and action. Disclosure of interest: None Declared. References: Neale JR, Basford PJ. General medical training in gastroenterology: views from specialist trainees on the challenges of dual accreditation. Clin Med. 2015;15(1):35–9 http://www.thejag.org.uk/Units/FAQs.aspx